Material extrusion of biomaterials for transformative biomedical applications - Wan Sharuzi, Wan Harun; Juliana, Jumadi; Shaghlil, Lena; Kadirgama, Kumaran; Safian, Sharif; Farhana, Mohd Foudzi; Thirugnanasambandam, Arunkumar; Md Hazrat, Ali; Fujio, Tsumori (Elsevier B.V., 2025)
Material extrusion (MEX) has emerged as a pivotal additive manufacturing modality, catalysing advancements in materials science and biomedical engineering. While numerous reviews have catalogued the progress in this field, a critical analysis of the inherent tensions and co-dependencies that govern its evolution is lacking. This review provides a unique synthesis by deconstructing the complex co-evolutionary dynamic between MEX technologies and biomaterial science, moving beyond descriptive accounts to critically examine the trade-offs between manufacturing speed, resolution, and biological functionality. We analyse the paradigm shift from bio-inert scaffolds to bio-instructive systems and confront the ‘personalisation paradox’, wherein bespoke patient-specific therapies challenge traditional validation and regulatory frameworks. Key applications in tissue engineering, personalised medical devices, and advanced in vitro models are evaluated not only for their achievements but also for the profound challenges they expose, particularly concerning functional maturation and vascularisation. By integrating these critical viewpoints with an analysis of future directions, including 4D bioprinting, AI-driven biofabrication, and in situ printing, this review articulates that the transformative potential of MEX hinges on resolving longstanding technological, material, and translational hurdles through focused, interdisciplinary collaboration.